ESTIMASI NILAI DOSIS RADIASI EFEKTIF PASIEN DARI CITRA MEDIS CT SCAN ASTEION MULTI 32 SLICE BAGIAN ABDOMEN - Nadiah Wanara; Muhammad Hamdi; Salomo Sinuraya (Universitas Riau, 2020)
Receipt of radiation doses in patients by CT scan media really contributed to the radio diagnostic field. So far, volume Computed Tomography Dose Index (CTDIvol) and Dose Length Product (DLP) are the dose parameters used as a prescription of the dose to the patients from the examination process on the CT scan. However, these parameters have the disadvantage that they only describe the dose output from the device without regard to patient size. Size Specific Dose Estimate (SSDE) is a dose correction based on patient size and an effective dose is the dose value that arises due to differences in biological sensitivity values. Calculation of SSDE values and total effective doses were carried out in this study from data of patients who had undergone an abdominal CT scan examination. Patient radiation dose data were obtained from documents collected from the Radiology Department at the Prima Pekanbaru hospital. The data was obtained from examination results of Toshiba Asterion Multi (CTB 400 tube) CT scan of the abdomen of 20 patients. The data analysis shows that the average value of SSDE for male and female patients are 19.64 mGy and 17.4 mGy and the average total effective dose for male and female patients are 12.63 mSv and 9.16 mSv. These data indicate that the level of radiation dose received by patients is below the threshold that has been evaluated based on BAPETEN provisions.